2001
DOI: 10.1046/j.1365-2346.2001.00863.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory acidosis does not increase plasma potassium in normokalaemic anaesthetized patients. A controlled randomized trial

Abstract: Acute respiratory acidosis does not affect plasma potassium concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
(35 reference statements)
1
10
0
Order By: Relevance
“…While a linear correlation between arterial carbon dioxide and plasma pH is well reported,39 the relationship between acute hypercapnia, respiratory acidosis and plasma potassium is also poorly understood 40. In the present study, we found no association between hypercapnia and serum potassium concentration, a finding also supported by others 41. We did not observe any other deleterious or adverse effects from hypercapnic-induced acidosis such as cardiac arrhythmias in our study.…”
Section: Discussionsupporting
confidence: 84%
“…While a linear correlation between arterial carbon dioxide and plasma pH is well reported,39 the relationship between acute hypercapnia, respiratory acidosis and plasma potassium is also poorly understood 40. In the present study, we found no association between hypercapnia and serum potassium concentration, a finding also supported by others 41. We did not observe any other deleterious or adverse effects from hypercapnic-induced acidosis such as cardiac arrhythmias in our study.…”
Section: Discussionsupporting
confidence: 84%
“…A more recent prospective randomised controlled trial by Natalini et al[8] examined plasma potassium in 17 normokalaemic anaesthetised patients who underwent either spontaneous-assisted ventilation or intermittent negative-pressure ventilation during interventional rigid bronchoscopy. Similar to our findings, the authors observed no association between increased extracellular H + and plasma potassium concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study differed in regard to surgical and anaesthetic procedures, patient populations and analysis. In particular, patients with coronary artery disease were specifically excluded in the Natalini et al[8] study, which is an important comorbidity in modern anaesthetic practice. In addition, only the relationship between potassium and H+ was discussed in the Natalini et al[8] paper, whereas our study also looked at the influence of PaCO 2 on potassium.…”
Section: Discussionmentioning
confidence: 99%
“…This study was limited by a small sample size and exposure to significant hypercarbia for only a 15 min duration. Similarly, Natalani et al [10] compared the acute changes in [K + ] p in acutely hypercapnic patients undergoing rigid bronchoscopy. The sampling time to evaluate the effects of PaCO 2 on hyperkalaemia was also of short duration (20 min), and acute respiratory acidosis did not affect [K + ] p .…”
Section: Discussionmentioning
confidence: 99%
“…potassium concentrations ([K + ] p ) is unclear with some studies showing an increase in concentration and others showing no effect [3][4][5][6][7][8][9][10]. Further, a body of longstanding evidence indicates that the hyperkalaemia-acidaemia relationship is more complex than the relatively simplistic, but commonly accepted notion that hyperkalaemia develops due to an increase in extracellular acidity and subsequent exchange of extracellular hydrogen ions for intracellular potassium ions [8].…”
mentioning
confidence: 99%